THE EFFECT OF THE USE OF GBFS AS A MEDIUM AGGREGATE SUBSTITUTION ON THE PERFORMANCE OF THE AC-WC ASPHALT MIXTURE - Panji Marshando (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2022)
The massive use of natural materials in major road infrastructure frequently disrupts the sustainability of the ecosystem in the environment. A solution for using other materials is needed to minimize the impact of using these natural materials. GBFS (Granulated Blast Furnace Slag) is waste from blast furnace combustion of iron and steel material in granular form, which characteristically can be used as a substitute for medium aggregate asphalt mixture material. The study was conducted by several testing, such as GBFS material testing, AC-WC asphalt mixture characteristic test using Absolute Density Method, and performance testing on AC-WC asphalt mixtures, based on its structural performance and dunctional performance with the percentage of GBFS as medium aggregate variation at 0%, 50%, 75%, and 100%. The study results show that the utilization of the percentage of GBFS as a medium aggregate substitution by 75% improves functional performance and structural performance of AC-WC asphalt mixture.Keyword: GBFS, Asphalt Mixture, AC-WC, Medium Aggregate.